Effect modification by dietary patterns in the relationship between slow gait and incident depressive symptoms: a 6-year cohort study of older Japanese adults (NISSIN Project) - Hao, Wen; Shan, Yi-fan; Kimura, Takashi; Ukawa, Shigekazu; Ohira, Hideki; Okabayashi, Satoe; Wakai, Kenji; Ando, Masahiko; Tamakoshi, Akiko (Frontiers in Nutrition, 2025)
IntroductionSlower gait speed is a well-established predictor of late-life depressive symptoms. Previous research suggests that diet can influence biological processes implicated in both gait decline and depression and may therefore serve as an effect modifier in their association. This study aimed to examine whether adherence to healthy dietary patterns modifies the relationship between gait speed and incident depressive symptoms in older adults.MethodsIn this longitudinal observational cohort study, we analyzed data from 1,887 depression-free, community-dwelling adults aged 64–65 years, obtained from the New Integrated Suburban Seniority Investigation (NISSIN) Project in Japan. Gait speed was self-rated at baseline as fast, normal, or slow. Dietary intake was assessed using a validated food frequency questionnaire (FFQ), and principal component analysis was performed to identify three dietary patterns: vegetables, Fat and Meat, and Bread and Egg. Incident depressive symptoms were defined as having a 15-item Geriatric Depression Scale (GDS-15) score of ≥6 after a 6-year follow-up. Modified Poisson regression was used to estimate relative risks (RRs), and interactions were assessed on multiplicative and additive scales.ResultsAfter 6 years, 12.5% of the participants developed depressive symptoms. Slow gait speed was significantly associated with a higher risk of depression (RR: 2.7; 95% CI: 1.6–4.6), while no dietary pattern was independently associated with depressive symptoms. This risk tended to be lower among slow walkers with higher adherence to a vegetable or Bread and Egg dietary pattern, although the interactions were not statistically significant. A significant negative interaction was found between slow gait and low adherence to a Fat and Meat diet on both additive (RERI = −2.5; 95% CI: −4.1 to −0.8) and multiplicative scales (Ratio of RRs: 0.3; 95% CI: 0.2–0.3).DiscussionDietary patterns may influence the link between slow gait and depression in older adults. Notably, reduced adherence to Fat and Meat diets was associated with a lower overall risk. These findings support dietary improvement as a scalable mental health strategy for physically vulnerable older adults.